Applying communication theory for professional life - Dainton, Marianne (SAGE, 2005)
Introduction to communication theory -- Explaining theories of intrapersonal communication -- Explaining theories of interpersonal communication -- Explaining theories of culture -- Explaining theories of persuasion -- Explaining theories of leadership -- Explaining theories of group communication -- Explaining theories of organizational communication -- Explaining theories of mediated communication -- So what should a communicator do?; Includes bibliographical references and index